A risk nomogram of COVID-19 infection in cancer patients (2020)
The pandemic of COVID-19 is of international concern and poses great challenges for management of oncology services.1 Recent studies showed that patients with cancer histories2 and cancer patients being treated3 had higher infection rates than individuals. Oncology societies have promptly issued guidelines on cancer care during the pandemic.1,4,5 These guidelines provide general recommendations to management of cancer patients, but offer no specific personal evaluations based on risk factors, which remain largely unstudied. Here, we have collected 27 confirmed cases from 1720 cancer patients in Renmin Hospital of Wuhan University, Wuhan, China during December 23, 2019 to January 23, 2020. Clinicopathologic and laboratory characteristics on routine admission were collected and analyzed to uncover the potential risk factors of COVID-19 infection. Univariate logistic analysis revealed that 17 factors were significantly associated with COVID-19 infection (Fig). Generally, older age, smoking history and primary site of liver were associated with increased risk. Besides, hypertension, radiation pneumonia and lung infection history were also significant risk factors (Fig). Notably, chemotherapy, radiotherapy, targeted therapy, and immunotherapy within 1 month were not risk factors in our analysis, while anemia and hypoproteinemia were statistically significant. In blood routine and chemistry test, low lymphocyte, rather than white blood cell, and platelet predicted increased risk. Meanwhile, nutritional status factors including hemoglobin, albumin, sodium, and potassium were also significant risk factors (Fig). In multivariate logistic analysis, hypertension (odds ratio [OR] = 5.18, 95% confidence interval [CI]: 1.10-24.98, P = 0.034), radiation pneumonia (OR = 17.71, 95% CI: 2.50-109.58, P = 0.002), lymphocyte count (OR = 0.07, 95% CI: 0.01-0.50, P = 0.018), and albumin (OR = 0.86, 95% CI: 0.76-0.96, P = 0.007) were independent risk factors for COVID-19 infection. Based on these 4 factors, a risk nomogram was built, and a total score over 120 indicated increased risk of COVID-19 infection. Notably, lymphocyte represented driven factor in the nomogram (Fig).